Intravitreal Aflibercept for Choroidal Neovascularization in Ocular Sarcoidosis. Issue 5 (September 2016) - Querques, Lea; Querques, Giuseppe; Miserocchi, Elisabetta; Modorati, Giulio; Bandello, Francesco
Purpose: To report a case of choroidal neovascularization (CNV) in a patient with ocular sarcoidosis treated by intravitreal aflibercept. Methods: A 27-year old man was referred to our department because of sudden visual acuity decrease (best-corrected visual acuity (BCVA) was 20/80 LE). Fundus examination showed bilateral optic disk swelling, retinal pigment epithelium changes at the posterior pole, yellowish chorioretinal lesions in the periphery, and the presence of a prominent peripapillary neovascular complex. Results: The clinical diagnosis was most compatible with ocular sarcoidosis, later confirmed by mediastinal lymph node biopsy. Fluorescein and indocyanine green angiography confirmed the presence of active peripapillary type 2 (classic) CNV in both eyes. Given that the exudation of the peripapillary CNV harmed the fovea, the patient underwent a single intravitreal aflibercept injection LE. One month after the treatment, LE BCVA decreased to 20/125. Spectral-domain optical coherence tomography (SD-OCT) showed complete resolution of subretinal fluid but revealed outer retinal atrophy with complete loss of the ellipsoid zone (EZ) in the macula (possibly responsible for visual acuity worsening). Six months later, LE BCVA slightly increased to 20/100, and SD-OCT showed partial recovery of the EZ in the macula. No adverse events related to the treatment were recorded during follow-up. Conclusions: We report a case of CNV in a patient with ocular sarcoidosis treated with intravitreal aflibercept. In our experience, intravitreal aflibercept injection achieved morphologic resolution for sarcoid-related peripapillary CNV.